Off-label use of canakinumab in pediatric rheumatology and rare diseases - Del Giudice, Emanuela; Sota, Jurgen; Orlando, Francesca; Picciano, Ludovica; Cimaz, Rolando; Cantarini, Luca; Mauro, Angela (Frontiers in Medicine, 2022)
Since the first success of interleukin-1 blockade in cryopyrin-associated periodic syndrome, interleukin-1 inhibitors use has expanded to other disorders, including off-label indications. In particular, canakinumab has been employed in an off-label fashion in several diseases such as rare monogenic autoinflammatory diseases and multifactorial autoinflammatory diseases, disclosing an excellent efficacy and good safety profile in pediatric patients unresponsive to standards of care. In addition, hyperferrinitinemic syndromes and complex disorders, namely diabetes, Kawasaki disease and uveitis represents other areas where canakinumab efficacy is worth exploring. Altogether, results summarized below are of paramount importance in pediatric patients where a considerable proportion of treatments are prescribed off-label. This review focuses on the off-label use of canakinumab in pediatric patients affected by systemic immune-mediated diseases.